Immunohistochemical Analysis of Sperm Aquaporin-3 Expression in Men with Varicocele - Duran, Senem Çetin; Akkuş, Murat; Duran, Enis; Aşır, Fırat; Dönmezdil, Nilüfer; Yıldızhan, Eda; Konk, Dilara; Uçkan, Kazım (Journal of Drug Delivery and Therapeutics, 2024)
Objective: The primary objective of this study is to detect potential alterations in sperm cells in cases of varicocele using immunohistochemical methods.Materials and Methods: In this study, semen samples obtained with consent from infertile males aged between 25-40 years were analyzed for the presence of varicocele and other determined factors, and were divided into two groups: a normozoospermic control group and a group diagnosed with varicocele. Direct swim-up techniques were utilized to separate spermatozoa with high motility. Immunohistochemical staining methods were employed to visualize protein expression, and the results were photographed at high magnification for documentation.Results: This research was conducted on sperm samples collected from males diagnosed with varicocele and from a healthy control group. The findings suggest that the presence of aquaporin-3 protein is associated with low or negative expression in sperm cells in the presence of varicocele. Immunohistochemical analyses have revealed a reduced or absent expression of aquaporin 3 in patients with varicocele compared to healthy individuals.Conclusion: The results of this study clearly demonstrate the adverse effects of varicocele on the structural and functional integrity of spermatozoa. Given that aquaporin-3 protein is critical for the motility of spermatozoa, the reduced expression or absence of this protein sheds light on the molecular mechanisms of male infertility.Keywords: Sperm DNA fragmentation, immunohistochemistry, Varicocele, protein expression, male infertility, aquaporin-3.